TRANSFORMASI UKM KE BISNIS ONLINE DENGAN INTERNET MARKETING TOOLS - Kursehi Falgenti (LPPM, 2011)
One of the efforts by the government, in this case Ministry of Cooperative and SMEs to introduce the world of internet marketing to the SMEs is to facilitate the trading board in www.indonesian-products.biz. This effort is to identify SME to conduct transactions online. There are still many other aspects in the internet marketing world to be known by SMEs. This paper will discuss low cost techniques and tools which can be exploited in the marketing of SME products and services. One is utilizing tools from Google. Other techniques are also needed to be able to dominate the Internet market. This paper will be accompanied by a company that has successfully sold Air Conditioner components over the Internet by utilizing marketing techniques and tools of internet. Key Words: UKM, Internet Marketing, bisnis online